Pengaruh Gaya Kepemimpinan Otokrasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Hotel Amans - Pieter Novry Ruddy Rehatta; Saleh Tutupoho; Asiani Sijabat; Meike Rehatta (Shofanah Media Berkah, 2023)
The purpose of this research is to determine the influence of the variables Autocratic Leadership Style and Work Discipline on Employee Performance at the Amans Hotel. The sample in this study was 51 Hotel Amans employees using the census method and the data collected was analyzed using descriptive and inferential statistics using SPSS Multiple Regression Analysis. The research results show that Autocratic Leadership Style and Work Discipline have a significant positive effect on Employee Performance at the Amans Hotel. The findings of this research indicate that Autocratic Leadership Style and increasingly improving Work Discipline will have a positive impact on employee performance at the Amans Hotel.